2019
DOI: 10.3390/socsci8020037
|View full text |Cite
|
Sign up to set email alerts
|

Big IFs in Productivity-Enhancing Industry 4.0

Abstract: With the dawn of Industry 4.0, its productivity-boosting impact appears to be comfortably ensconced both in the media and in the scientific community. Still, our paper is to portend a rather dismal prognosis by outlining three big Inertia Forces (IFs) hindering the power of Industry 4.0 in reviving productivity growth in a more spectacular way. After applying a complexity view to the development of Industry 4.0 in deciphering the major IFs, the paper briefly exemplifies them by building on the case of Hungary,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…When it comes to drivers and barriers affecting implementation, this question has received some attention in recent contributions about I4.0 in SMEs (Stentoft et al 2001;Türkes , et al 2019;Vrchota et al 2019). Related to this, researchers recognize that there is range of managerial and organizational challenges (Agostini and Filippini 2019) and inertia forces (Kovacs 2019) which can make it difficult to succeed with the adoption and implementation of I4.0. Sony and Naik (2019) argue that most organizations lack a detailed understanding of the I4.0 concept, which perhaps is not surprising in light of the review in Section 3 of this paper which showed that there is a large number of definitions of the concept in the literature (Moeuf et al 2018).…”
Section: Adoption and Implementationmentioning
confidence: 99%
“…When it comes to drivers and barriers affecting implementation, this question has received some attention in recent contributions about I4.0 in SMEs (Stentoft et al 2001;Türkes , et al 2019;Vrchota et al 2019). Related to this, researchers recognize that there is range of managerial and organizational challenges (Agostini and Filippini 2019) and inertia forces (Kovacs 2019) which can make it difficult to succeed with the adoption and implementation of I4.0. Sony and Naik (2019) argue that most organizations lack a detailed understanding of the I4.0 concept, which perhaps is not surprising in light of the review in Section 3 of this paper which showed that there is a large number of definitions of the concept in the literature (Moeuf et al 2018).…”
Section: Adoption and Implementationmentioning
confidence: 99%
“…42 Bénassy-Quéré et al (2019) gave a very good account on the disappointing reform will regarding the Eurozone. 43 See Kirman (2010) or for a more detailed discussion on complexity economics, see Kovács (2019 -forthcoming).…”
Section: Discussionmentioning
confidence: 99%
“…9 The backlash against globalisation that is to say the ailing trust infrastructure is due to the interplay among intertwined wicked challenges. Since a more comprehensive account was given to these complex challenges elsewhere (Kovács 2019), we just mention them: climate change; demographic challenges (i.e. not only the issue of aging population as well as migration crisis, but also the runaway of income and wealth inequalities are of key importance in creating serious instabilities 10 ); the runaway of the financial sector at the expense of the real economy (i.e.…”
Section: Great Moderation and The Emergence Of Critical Instabilitiesmentioning
confidence: 99%
“…The sustainable supply chain, and simultaneously 4.0, can be defined as the supply chain that uses Industry 4.0 tools in order to close the material and energy cycles, besides helping the information flow and the activities, turning the operations more efficient, more intelligent, more precise, and quicker. Kovacs [22] reinforces the educational aspects for human resource development, creating skills, and the knowledge to deal with the digital economy. These educational aspects promote the fourth industrial revolution changes on the productions and on the organizations [23].…”
Section: Theoretical Backgroundmentioning
confidence: 99%